2019
DOI: 10.2807/1560-7917.es.2019.24.6.1700774
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rotavirus vaccination on rotavirus genotype distribution and diversity in England, September 2006 to August 2016

Abstract: Introduction Rotavirus vaccination with the live-attenuated monovalent (a G1P[8] human rotavirus strain) two-dose Rotarix vaccine was introduced in England in July 2013. Since then, there have been significant reductions in rotavirus gastroenteritis incidence. Aim We assessed the vaccine’s impact on rotavirus genotype distribution and diversity 3 years post-vaccine introduction. Methods Epidemiological and microbiological data on genotyped ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
75
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(86 citation statements)
references
References 39 publications
7
75
2
Order By: Relevance
“…In 2017, G2P [4] (40.0 ) was the most prevalent strain, followed by G3P [8] (DS-1-like) (28.0 ), G8P [8] (10.0 ), G3P [8] (Wa-like) (8.0 ), G9P [8]-E1 (8.0 ), and mixed infection (6.0 ). In 2018, G3P [8] (DS-1-like) (28.6 ) and G9P [8]-E2 (28.6 ) were the most prevalent strains, followed by G9P [8]-E1 (19.0 ), G2P [4] (9.5 ), G8P [8] (9.5 ), and mixed infection (4.8 ). Six G9P [8]-E2 strains detected in 2018 showed an atypical genotype constellation (G9-P[8]-I1-R1-C1-M1-A1-N1-T1-E2-H1), which had not been reported previously.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In 2017, G2P [4] (40.0 ) was the most prevalent strain, followed by G3P [8] (DS-1-like) (28.0 ), G8P [8] (10.0 ), G3P [8] (Wa-like) (8.0 ), G9P [8]-E1 (8.0 ), and mixed infection (6.0 ). In 2018, G3P [8] (DS-1-like) (28.6 ) and G9P [8]-E2 (28.6 ) were the most prevalent strains, followed by G9P [8]-E1 (19.0 ), G2P [4] (9.5 ), G8P [8] (9.5 ), and mixed infection (4.8 ). Six G9P [8]-E2 strains detected in 2018 showed an atypical genotype constellation (G9-P[8]-I1-R1-C1-M1-A1-N1-T1-E2-H1), which had not been reported previously.…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, G3P [8] (DS-1-like) (28.6 ) and G9P [8]-E2 (28.6 ) were the most prevalent strains, followed by G9P [8]-E1 (19.0 ), G2P [4] (9.5 ), G8P [8] (9.5 ), and mixed infection (4.8 ). Six G9P [8]-E2 strains detected in 2018 showed an atypical genotype constellation (G9-P[8]-I1-R1-C1-M1-A1-N1-T1-E2-H1), which had not been reported previously. Phylogenetic analyses suggested that the RVA virus was generated by inter-genogroup reassortment between commonly circulating G9P [8] and G2P [4] strains in Japan.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations